The Immigrant and the University : Peder Sather and Gold Rush California - Sveen, Karin, 1948- (Book collections on Project MUSE., 2014)
Peder Sather was a scribe before he emigrated from Norway to New York in 1832. There, he worked as a servant and a clerk at a lottery office before opening an exchange brokerage. During the gold rush, he moved to San Francisco to help establish the banking house of Drexel, Sather & Church on Montgomery Street. Sather was a founder and a liberal benefactor of the University of California at Berkeley where he is memorialized by the Sather Gate and Sather Tower (the Campanile), three endowed professorships, and more recently the Peder Sather Center for Advanced Study. Karin Sveen, one of Norway's.